Physiotherapy management in patients with sleep apnea - a systematic review - Pagar, Mansi A.; Gunjal, Sambhaji B. (International Journal of Research in Medical Sciences, 2025)
Sleep apnea, particularly obstructive sleep apnea (OSA), is a common disorder associated with various systemic health complications. Recent studies have highlighted the role of physiotherapy in managing OSA symptoms and improving patient outcomes. However, the effectiveness of physiotherapy interventions remains unclear. This systematic review aims to: assess the current literature on physiotherapy management in patients with sleep apnea, evaluate the effectiveness of various physiotherapy interventions in alleviating sleep apnea symptoms, and to identify gaps in research and suggest areas for future studies. The study period was from February 2024 to February 2025. A comprehensive literature search was conducted in databases including PubMed, Cochrane, CINAHL, and PEDro, following PRISMA guidelines. Studies published from 2015 to 2024 were considered, focusing on randomized controlled trials (RCT), cohort studies, and systematic reviews. A total of 20 studies met the initial inclusion criteria. After applying the exclusion filters, 15 studies were included in the final review. The findings indicated that physiotherapy interventions, such as continuous positive airway pressure (CPAP) therapy adjuncts, inspiratory muscle training, and sleep posture training, showed positive outcomes in reducing apnea severity, improving sleep quality, and enhancing daytime functioning. Physiotherapy interventions offer promising benefits in the management of sleep apnea, particularly in improving the quality of sleep and reducing symptom severity. However, further high-quality studies are needed to determine the long-term effectiveness and best physiotherapy protocols for sleep apnea management.